2024
DOI: 10.3389/fonc.2023.1216326
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning models for image-based gynecological cancer diagnosis: a systematic review and meta- analysis

Asefa Adimasu Taddese,
Binyam Chakilu Tilahun,
Tadesse Awoke
et al.

Abstract: IntroductionGynecological cancers pose a significant threat to women worldwide, especially those in resource-limited settings. Human analysis of images remains the primary method of diagnosis, but it can be inconsistent and inaccurate. Deep learning (DL) can potentially enhance image-based diagnosis by providing objective and accurate results. This systematic review and meta-analysis aimed to summarize the recent advances of deep learning (DL) techniques for gynecological cancer diagnosis using various images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Initial studies have explored the potential of artificial intelligence methods such as machine and deep learning in gynecological imaging overall, as well as in endometriosis and adenomyosis, and the findings appear promising [36][37][38][39][40]. For instance, in a sonographic preliminary study, a deep learning model showed a lower accuracy but a higher specificity in diagnosing adenomyosis on ultrasonographic images compared to intermediate-skilled trainees [36].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have explored the potential of artificial intelligence methods such as machine and deep learning in gynecological imaging overall, as well as in endometriosis and adenomyosis, and the findings appear promising [36][37][38][39][40]. For instance, in a sonographic preliminary study, a deep learning model showed a lower accuracy but a higher specificity in diagnosing adenomyosis on ultrasonographic images compared to intermediate-skilled trainees [36].…”
Section: Discussionmentioning
confidence: 99%
“…Arti cial intelligence (AI) has emerged as a signi cant tool with diverse medical applications (Wang et al, 2024). Deep learning (DL) can quantitatively analyze of medical images and has been applied in the eld of oncology (Taddese et al, 2024). Several studies demonstrated that DL can improve the diagnosis, predict treatment responses, and progression-free survival of patients with ovarian tumors (Arezzo et…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) has emerged as a significant tool with diverse medical applications (Wang et al 2024 ). Deep learning (DL) can quantitatively analyze of medical images and has been applied in the field of oncology (Taddese et al 2024 ). Several studies demonstrated that DL can improve the diagnosis, predict treatment responses, and progression-free survival of patients with ovarian tumors (Arezzo et al 2022 ; Boehm et al 2022 ; Na et al 2024 ; Sadeghi et al 2024 ; Yao et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%